The Influence of Green Marketing on Purchase Intention of Eco-Friendly Household Products: The Mediating Role of Consumer Rights Awareness - Muhamad Al Faruq Abdullah; Eriklex Donald (Green Publisher, 2025)
This study aims to examine the influence of green marketing on consumers' purchase intention of eco-friendly household products, with consumer rights awareness as a mediating variable. Using a quantitative approach, data were collected through an online survey of 100 respondents aged 18–35 who are aware of sustainable products. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that green marketing has a significant and positive effect on both consumer rights awareness (? = 0.834; p < 0.001) and purchase intention (? = 0.541; p < 0.001). Additionally, consumer rights awareness has a positive influence on purchase intention (? = 0.355; p = 0.003) and significantly mediates the relationship between green marketing and purchase intention (? = 0.296; p = 0.006). These findings highlight the dual function of green marketing as both an informative and empowering tool in sustainable consumption. The study contributes to the understanding of how ethical communication strategies can enhance behavioral outcomes and provides practical implications for businesses aiming to increase market adoption of environmentally friendly products.